Territory - city - university (2011)
This essay questions the ways in which universities are affected by the transformations produced within contemporary cities. The system of mutual relations between both is analysed through the following three factors: the high flux of communications, the hyper mobility of capital, and economic globalization. These become the principal thread of the two first parts of the essay. As a final reflection, the university-city relationship in Bogota is considered. Comparisons are made between the possible benefits or deficiencies of two models of university space; those which possess a campus and those which are inserted within the urban fabric, but do not have a campus.